Delayed‐phase thrombocytopenia in patients with coronavirus disease 2019 (COVID‐19). (18th June 2020) - Chen, Wanxin; Li, Ziping; Yang, Bohan; Wang, Ping; Zhou, Qiong; Zhang, Zhiguo; Zhu, Jianhua; Chen, Xuexing; Yang, Peng; Zhou, Hao
Summary: Coronavirus disease 2019 (COVID‐19) can affect the haematopoietic system. Thrombocytopenia at admission was prevalent, while late‐phase or delayed‐phase thrombocytopenia (occurred 14 days after symptom onset) is rare. This retrospective, single‐centre study screened 450 COVID‐19 patients and enrolled 271 patients at the Union Hospital, Wuhan, China, from January 25 to March 9, 2020. COVID‐19‐associated delayed‐phase thrombocytopenia occurred in 11·8% of enrolling patients. The delayed‐phase thrombocytopenia in COVID‐19 is prone to develop in elderly patients or patients with low lymphocyte count on admission. The delayed‐phase thrombocytopenia is significantly associated with increased length of hospital stay and higher mortality rate. Delayed‐phase nadir platelet counts demonstrated a significantly negative correlation with B cell percentages. We also provided and described bone marrow aspiration pathology of three patients with delayed‐phase thrombocytopenia, showing impaired maturation of megakaryocytes. We speculated that immune‐mediated platelet destruction might account for the delayed‐phase thrombocytopenia in a group of patients. In addition, clinicians need to pay attention to the delayed‐phase thrombocytopenia especially at 3–4 weeks after symptom onset.